A Note on the Ages of the Alkaline Rocks of the Peshawar Plain Alkaline Igneous Province, NW Pakistan - Kempe, D.R.C. (Journal of Himalayan Earth Sciences, 1986)
The available ages published for the alkaline rocks and carbonatites of the Peshawar Plain alkaline igneous province are reviewed with no new data and briefly discussed. Repeated magmatism has apparently occurred, over the period ca 315 to 31 m.y. ago, due to rifting and the development of thrust planes.